Academic Benchmarks for Otolaryngology Leaders. (August 2015) - Eloy, Jean Anderson; Blake, Danielle M.; D'Aguillo, Christine; Svider, Peter F.; Folbe, Adam J.; Baredes, Soly
Objective: This study aimed to characterize current benchmarks for academic otolaryngologists serving in positions of leadership and identify factors potentially associated with promotion to these positions. Methods: Information regarding chairs (or division chiefs), vice chairs, and residency program directors was obtained from faculty listings and organized by degree(s) obtained, academic rank, fellowship training status, sex, and experience. Research productivity was characterized by (a) successful procurement of active grants from the National Institutes of Health and prior grants from the American Academy of Otolaryngology–Head and Neck Surgery Foundation Centralized Otolaryngology Research Efforts program and (b) scholarly impact, as measured by the h-index . Results: Chairs had the greatest amount of experience (32.4 years) and were the least likely to have multiple degrees, with 75.8% having an MD degree only. Program directors were the most likely to be fellowship trained (84.8%). Women represented 16% of program directors, 3% of chairs, and no vice chairs. Chairs had the highest scholarly impact (as measured by the h-index ) and the greatest external grant funding. Conclusion: This analysis characterizes the current picture of leadership in academic otolaryngology. Chairs, when compared to their vice chair and program director counterparts, had more experience and greater research impact. Women were poorly represented among all academic leadership positions.